(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, riproduce il testo dell’intervento nel dibattito a due voci (con il presidente della Corte costituzionale, Gaetano Silvestri) a conclusione del convegno “La Bibbia sulle strade dell’uomo” (Messina, 23 novembre 2013), ed è destinato alla pubblicazione negli Atti. SOMMARIO: 1. L’etica civile come etica costituzionale – 2. L’etica evangelica – 3. Irriducibilità? – 4. La promessa e il terzo – 5. La libertà – 6. Il tratto di cammino insieme. Civil Ethic and Evangelical Beatitudes ABSTRACT The differences between civil ethic and religious ethic, that the Author defines as constitutional principles and evangelic Beatitudes, are well known: it’s common knowledge that the ones are effective in the earthly life while the others are oriented to the eternal life. Nevertheless the Author argues that they both have a common feature before that last analysis: they cross as principles of continuing opposition to unjust society, to “unlawful law”, to spreading apart between the constitutional and evangelic must be and the legislative being of positive law. KEY-WORDS: Civil Ethic – Constitution – Evangelical Beatitudes – Differences - Common Feature.